The importance of resilience and coherence in dealing with the COVID-19 pandemic among medical and non-medical students - Agnieszka Syrowatko; Krzysztof Zdziarski (Kazimierz Wielki University, 2021)
The aim of the study is to determine the level of resilience and coherence as well as the type of affective reactions manifested among students of medical and non-medical faculties, as well as to analyze potential predictors of the intensification of positive and negative reactions to the COVID-19 pandemic.